2016
DOI: 10.1021/jacs.6b05333
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of the Role of O2 and H2O in the Decoupling of Graphene on Cu(111)

Abstract: The structural and electronic properties of graphene coated on a Cu(111) surface can be strongly influenced by the arrangement of adsorbates at the graphene edges. Oxygen and water intercalation at the graphene edges could lead to oxidation and hydrolysis at the graphene/Cu(111) interface, eventually causing decoupling of graphene from the Cu substrate. However, the reaction pathways for oxygen or water (or both) intercalation at the graphene edges are not well understood at the molecular level. Using ab initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 67 publications
(115 reference statements)
1
16
0
Order By: Relevance
“…6 . In the final state, the right side of graphene is totally decoupled with SiC surface, which is similar to the results of previous study 36 . It is found that the energy barrier is very small (~0.06 eV) and the total energy of final state is 0.85 eV lower than the initial state, thus this process would happen very easily in experiments.…”
Section: Resultssupporting
confidence: 90%
“…6 . In the final state, the right side of graphene is totally decoupled with SiC surface, which is similar to the results of previous study 36 . It is found that the energy barrier is very small (~0.06 eV) and the total energy of final state is 0.85 eV lower than the initial state, thus this process would happen very easily in experiments.…”
Section: Resultssupporting
confidence: 90%
“…The Please do not adjust margins Please do not adjust margins second hypothesis is based upon chemical reactivity -water is a comparatively reactive molecule and molecular nitrogen is highly inert. H2O is known to dissociate at edge sites 46 , with reports that the graphene edge sites may in fact reduce the activation energy for H2O dissociation, compared to bare Cu 47 . It is possible that this decomposition is followed by hydroxyl diffusion across the surface, providing a route for H2O to escape.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the existence of oxidants plays important roles in modulating the graphene growth. First, H 2 O and O 2 molecules adsorb onto the Cu surface, leading to the cleavage of O–O and O–H bonds to decompose into O species (O and OH radicals) at high growth temperature via coupled reactions: , We consider O and OH radicals as O-containing species because graphene growth is highly sensitive to them and the coupled reactions are more energetically favorable. Disassociated O species on the Cu surface essentially have two possibilities of existence where they either diffuse on the Cu surface or dwell at energetically favorable sites via the formation of stable chemical bonds with the surface Cu atoms. On average, the former is responsible for etching C from the graphene lattice by random collision, and the latter is associated with the promoted nucleation of graphene.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the existence of oxidants plays important roles in modulating the graphene growth. First, H 2 O and O 2 molecules adsorb onto the Cu surface, leading to the cleavage of O−O and O−H bonds to decompose into O species (O and OH radicals) at high growth temperature via coupled reactions:22,23…”
mentioning
confidence: 99%